DINAMIKA PEMBIAYAAN PERBANKAN SYARIAH DALAM MENGEMBANGKAN DUNIA USAHA - Muhammad Soekarni (Jurnal Ekonomi dan Pembangunan, 2025)
This paper discusses Islamic banking financing distributed by type of use, the business sector, and schemes. Analysis is performed at the macro and the micro level. Macro analysis uses secondary data from Islamic Banking Directorate of Bank Indonesia, while the micro analysis is based on case studies of one Islamic bank. Performance of Islamic banking financing, particularly distributed by Sharia Commercial Bank and Sharia Business Unit Operations, at the macro level was quite good. This achievement demonstrated by the highly growth rate of financing; non performing financing still within safe limits set by BI and tend to get smaller in the past two years, and the distribution of financing for the working capital and investment continues to grow. However, while the allocation of financing for consumption has increased rapidly since the year 2008, the portion to support productive activities began to decline. Moreover, financing scheme still nominated by the trade-based contract (murabaha), and was concentrated on SME’s level and service sectors.